2020
DOI: 10.18632/aging.103770
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Lactate Dehydrogenase (LDH) level as an independent risk factor for the severity and mortality of COVID-19

Abstract: Early identification of severe patients with coronavirus disease 2019 (COVID-19) is very important for individual treatment. We included 203 patients with COVID-19 by propensity score matching in this retrospective, case-control study. The effects of serum lactate dehydrogenase (LDH) at admission on patients with COVID-19 were evaluated. We found that serum LDH levels had a 58.7% sensitivity and 82.0% specificity, based on a best cut-off of 277.00 U/L, for predicting severe COVID-19. And a cut-off of 359.50 U/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 20 publications
9
87
0
2
Order By: Relevance
“…Regarding blood chemistry, hs-CRP is a major biomarker that represents acute phase inflammation [ 2 , 10 , 14 - 17 ]. LDH is related to cell damage, so elevated LDH is an independent risk factor for the severity and mortality of COVID-19 [ 2 , 8 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding blood chemistry, hs-CRP is a major biomarker that represents acute phase inflammation [ 2 , 10 , 14 - 17 ]. LDH is related to cell damage, so elevated LDH is an independent risk factor for the severity and mortality of COVID-19 [ 2 , 8 - 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding blood chemistry, hs-CRP is a major biomarker that represents acute phase inflammation [ 2 , 10 , 14 - 17 ]. LDH is related to cell damage, so elevated LDH is an independent risk factor for the severity and mortality of COVID-19 [ 2 , 8 - 11 ]. Hypoalbuminemia [ 18 , 20 , 21 ], hypocalcemia [ 31 - 33 ], and elevated aspartate aminotransferase [ 18 ] are highly associated with severe COVID-19 infection requiring hospitalization in the intensive care unit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies demonstrated that there was an association between LDH values and worse outcomes in COVID-19 patients. Li et al found that elevated serum LDH at admission remained a more independent risk factor among the other in ammatory markers for COVID-19 severity and mortality [23]. Therefore, we suggest that elevated serum LDH levels in both acute and chronic phase may be used as an important tool in determining clinical outcomes and prognosis in COVID-19.…”
Section: Discussionmentioning
confidence: 63%